FAKTOR – FAKTOR YANG MEMPENGARUHI RASIO PERUBAHAN LABA PADA PT. INDOFOOD SUKSES MAKMUR TBK. - Nurul Adira Safitri Safitri (Universitas Merdeka Madiun, 2022)
In this study found a problem, namely Asset Value, Debt Value and Profit Value at PT. Indofood Sukses Makmur Tbk. experiencing fluctuations. This study aims to determine the effect of Current Ratio, Debt to Equity Ratio, and Return On Assets to changes in earnings and the purpose to determine the effect of Current Ratio, Debt to Equity Ratio, and Return On Assets to changes in earnings. a list of tables in the form of financial statements containing the Statement of Net Profit, Gross Profit, Net Sales, Total Equity, Total Liabilities and Total Assets. The population is 20 years and the sample is 15 years. The object of this research is located at PT. Indofood Sukses Makmur, Tbk with its address at Sudirman Plaza, Indofood Tower, 21st Floor. The data collection techniques in this research are library and documentation studies. This data analysis was carried out with the help of the SPSS program, namely by performing multiple linear regression analysis through the requirements test, namely passing the classical assumption test consisting of normality test, multicollinearity test, heteroscedasticity test, autocorrelation test and hypothesis testing. Current Ratio (CR) has no significant effect on Changes in Profit. Return On Assets (ROA) has no significant effect on changes in profit. Debt to equity ratio (DER) has no significant effect on changes in earnings. and Current Ratio (CR), Return On Assets (ROA) and Debt to Equity Ratio (DER) have a simultaneous effect on Changes in Profit for Investors, the results of this study are expected to provide useful data in pursuing business choices. It is also believed that in making decisions not only depend on information related to the ratios contained in the study, but it is necessary to pay attention to other factors and ratios in relation to Profit Changes. For the company, it is expected to pay more attention to the company's ability to generate profits. For further researchers, it is expected to increase the variables and wider observations.